Effects of cigarette smoke condensate on the growth of and production of biofilm by Streptococcus pneumoniae and on the bioactivity of pneumolysin - Cockeran, Riana (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.